Reconstructing green school in Malaysia: an outdoor learning experience of Rainbow Troop and Toto Chan - Utaberta, Nangkula; Abdullah, Akmal Goh; Jaafar, Nor Haslina (Jabatan Seni Bina, Fakulti Kejuruteraan & Alam Bina, Universiti Kebangsaan Malaysia, 2014)
With current development in the pedagogy of teaching and learning approaches in the world, not many studies have been done on outdoor learning in Malaysia. Most of the study was focusing on the development of curriculum and the delivery of knowledge but not many writing and approaches has been done to see outdoor learning as one of the alternative methods of learning in school design. This paper tries to reconstruct a new framework for elementary school design in Malaysia by introducing a new typology called green school. By referring to the unique approaches of the Rainbow Troops in Indonesia and the story of Toto Chan’s outdoor learning space. It will challenge our perception of Malaysian common school design by introducing more open and outdoor oriented learning approaches. The discussion itself will consist of four (4) main parts First part will discuss on the current problem and situation in teaching and learning in Malaysia, while the second part will try to explore and review on the definition of outdoor learning with its importance and character in learning environment. The third part will focused on the lesson from Natural School approaches and philosophy of learning while the last part will do some analysis and on the 3rd year design studio in architecture department of Universiti Putra Malaysia.